A Model of Contagious Currency Crises with Application to Argentina - Choueiri, Nada. (Washington, D.C. : International Monetary Fund, 1999)
This paper proposes a model of contagious currency crises: crises transmit across countries by raising the risk premium on government bonds. Three types of equilibria can occur: a 'no-collapse' equilibrium (crises never transmit from abroad); a 'collapse' equilibrium (crises are inevitably contagious); or a 'fundamentals' equilibrium (crises are contagious if domestic fundamentals are weak). A calibration exercise finds that the 1995 turmoil in Argentina coexisted with a combination of risk-averse investors and weak credibility in the currency board arrangement. This turmoil could only be attributed to a Tequila effect from the Mexican crisis alone if investors were excessively risk-averse.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet